Upaya Meningkatkan Life Skill Melalui Permainan Futsal Pada Siswa SMK Darussalam Karangpucung - Dian Imam Saefulah; Rama Cipta Prasetia; Gilang Anggoro (Pusat Riset dan Inovasi Nasional, 2021)
This research aims to determine the influence and differences in the development of life skills of students who take part in extracurricular futsal. The population in this study was 30 students who took part in extracurricular futsal. The sample used was 20 students taken using purposive sampling technique, who were divided into two groups, namely the experimental group and the control group. The experimental group was given futsal game treatment that integrated life skills while the control group was given futsal game treatment that was not integrated life skills. The instrument used was a life skills questionnaire. Test the research data using paired sample t-test and independent sample t-test with the help of SPSS version 25 software. The research results show (1) The sig value is 0.000 < 0.05, which means there is a significant influence between before treatment and after treatment in the group. given futsal game treatment that integrates life skills. (2) A sig value of 0.000 < 0.025 means that there is a significant difference between the experimental group that was given futsal game treatment that integrated life skills, and the control group that was given futsal game treatment that was not integrated with life skills. Based on the research results, it can be concluded that there was a significant increase in the experimental group that was given futsal game treatment that was integrated with life skills. Because in practice students are given material about life skills at every meeting and do it repeatedly. Keywords: Life Skills, Futsal Game, Life Skills Integration, Life Skills Development